(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2017)
Urban and microclimate have intense relationship that affecting each other’s. Specific urban structure can affect microclimate because of high radiation generated. In the other side, urban structure blocks distribution of incoming wind. Urban structure changes how the microclimate influences the city. The successful urban structure can impact how outdoors open spaces are used meanwhile good open spaces are affected by how comfortable can be accepted. Microclimate control is the first element has to be considered to design comfortable outdoor open spaces. This research used monthly mean air temperature, relative humidity, precipitation, vapor pressure, and wind velocity for the period 2009–20014 to simulate any type of microclimate situation that influence thermal comfort in the urban context. Data were collected from 3 selected meteorological stations in Jakarta and websites. PET (physiological equivalent temperature) is used to assess the value of thermal comfort in outdoor spaces. This study shows that hot-humid city has abundance solar radiation, which influences the heat in the urban area that need to be released immediately meanwhile because of the urban structure reduce the wind velocity that enter into the urban area, the city does not has strong energy to release the heat. So urban structure has to be well designed to make wind can release the heat trapped in the urban area.